Critical Thinking Ability: Analysis of Flat Mirror Reflection Material - Erda Purwanti; Heldalia Heldalia (Schrödinger: Journal of Physics Education, 2023)
Research Objectives: The aim of this study was to analyze students' critical thinking skills in the reflection material on plane mirrors. The instrument used in this research is a matter of critical thinking skills Methodology: This type of research uses qualitative and quantitative research. With a sample of 84 students. Data were analyzed using the SPSS 23 program to obtain the mean, mode, median, maximum and minimum. Main Findings: Based on the results of this study, students' critical thinking skills are still low. Because students are less enthusiastic in the learning process, students also do not respond optimally to these problems, the student's concept understanding factor is still low, causing misconceptions. Novelty/Original Research: The novelty in this study is in the form of an analysis of students' critical thinking skills in the material of plane mirror reflection.